2005
DOI: 10.2217/14622416.7.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling Associated with Recurrence in Patients with Rectal Cancer Treated with Chemoradiation

Abstract: Genomic profiling may help to identify patients who are at high risk for developing tumor recurrence, and those who are more likely to benefit from chemoradiation therapy. A larger prospective study is needed to validate these preliminary data using germline polymorphisms on tumor recurrences in rectal cancer patients treated with chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…Li et al (2006) analyzed pancreatic cancer treated with radiotherapy and did not find any association between this polymorphism and survival. Likewise, Gordon et al (2006) studied rectal cancer and did not report an association of this polymorphism with disease relapse, lymph node status or chemotherapy response, which concurs with our results. We found that the C allele is associated with worse prognosis, but this is not related to radiotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…Li et al (2006) analyzed pancreatic cancer treated with radiotherapy and did not find any association between this polymorphism and survival. Likewise, Gordon et al (2006) studied rectal cancer and did not report an association of this polymorphism with disease relapse, lymph node status or chemotherapy response, which concurs with our results. We found that the C allele is associated with worse prognosis, but this is not related to radiotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous data and others have shown that the IL-8/CXCR2 pathway plays a key role in mediating colorectal cancer development (11,14,15,32). In follow-up to our previously published data in colorectal cancer, this study focused on the impact of inhibition of CXCR2 on the proliferation, survival, invasion, and migration in colorectal cancer in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 90%
“…Although the detail mechanisms for individual difference in radiotherapy remained unknown, genetic polymorphisms were demonstrated to be one of the major factors influencing the radiotherapy, especially the genetic polymorphisms of DNA repair genes (Gordon et al, 2006;Terrazzino et al, 2006). DNA damage response plays a significant role in the biological effects of radiotherapy.…”
Section: Introductionmentioning
confidence: 99%